2022
DOI: 10.1089/whr.2021.0100
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators of and Barriers to Successful Implementation of the One Key Question® Pregnancy Intention Screening Tool

Abstract: Background: One Key Question ® (OKQ) is a tool that embeds a patient-centered screening into routine visits with the goal of making pregnancy intention screening universal, but widespread implementation has not yet been adopted. We aimed to explore the barriers and facilitators of OKQ implementation to better understand how to best implement the tool across different settings. Methods: We invited staff and clinicians from one obstetrics and gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…For example, one study found that in primary care settings, implementation of OKQ increased patient satisfaction. 16 This study also reported that 80% of care clinicians reported feeling that they were able to address a patient’s healthcare needs during visits where OKQ was deployed. 17–19 …”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…For example, one study found that in primary care settings, implementation of OKQ increased patient satisfaction. 16 This study also reported that 80% of care clinicians reported feeling that they were able to address a patient’s healthcare needs during visits where OKQ was deployed. 17–19 …”
Section: Introductionmentioning
confidence: 83%
“…Clinicians may be reluctant to adopt OKQ because of its potential to influence workflow, by increasing time concerns, slowing room turnover, or increasing visit time. 16 , 16 OKQ may also be viewed by clinicians as a distraction from the main goal of the appointment. For example, one family medicine physician noted that asking the OKQ, “totally derailed the visit”.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) If so, when do you think that might be?, and (3) How important is it to you to prevent pregnancy (until then)? One Key Question 73 might also be used to elicit patients' pregnancy intentions: Would you like to become pregnant in the next year?…”
Section: Shared Reproductive Decision Making Is Needed To Improve The...mentioning
confidence: 99%